Relationship between Corporate Disclosure Score and Different Corporate Determinants: Evidence from Conventional Banks in Bangladesh - Hossain, Md. Solaiman (Asian Business Review, 2022)
The main goal of this study is to evaluate the relationship between corporate disclosure scores and their different determinants. To achieve this aim, secondary data have been employed and collected from the five years annual reports of the ten sample banks. To reveal consolidated disclosure scores, this study used an unweighted disclosure checklist. It has been found that the mean value of the tight disclosure score of the sample bank_9 is 76.45 percent which is higher, and the lowest mean value of the consolidated disclosure score is 71.24 percent, which is visible in the case of sample bank_8. Furthermore, there is no significant variation in tight disclosure scores among the sample banks over the study period. This study has considered the various corporate determinants and employed the ANOVA test and multiple regression analysis to evaluate the relationship between the different corporate determinants and corporate disclosure scores. The results of the ANOVA test illustrated that there is significant variation in other determinants of corporate disclosure among the sample banks. The findings of multiple regression analysis indicate that the R square value is 0.717, which confirms that the dependent variable, like the level of corporate disclosure, is explained by 71.70% of the independent variables, such as total assets, total revenues, number of branches, number of employees, meal members, female members, independent directors, audit committee members, capital adequacy ratio, debt equity ratio, loan deposits ratio and debt assets ratio. The results of the model summary report that the significance level of the overall model is lower than 5%, which means that the entire independent variables have significantly influenced the corporate disclosure score.